Recent Publications Upon Economics (Quarterly Journal of Economics, 1907)
Journal Article Recent Publications Upon Economics Get access The Quarterly Journal of Economics, Volume 21, Issue 3, May 1907, Pages 503–518, https://doi.org/10.1093/qje/21.3.503 Published: 01 May 1907